Modeling the Emergence and Growth of Alligatorweed at Different Field Capacity Levels - AHMAD,T. (2020)
ABSTRACT: A study focusing on different field capacity levels was planned in the Weed Science Lab, Department of Agronomy, University of Agriculture Faisalabad. Fresh alligatorweed was harvested from the Agronomy fields and cuttings (2 cm length) were made from it. These cuttings were placed at 25%, 50%, 75% and 100% field capacity levels in pots for 25 days. The results of the experiments revealed that at all field capacity levels, fragments of alligatorweed were able to sprout and grow. Increased moisture levels significantly increased the emergence ability and survival of the alligatorweed plants upto a certain level. Compared with the control (25% FC), emergence time of the sprouts in the maximum moisture regime (100% of FC) decreased by 40% (12.94 days vs.7.17 days). By contrast, the survival rate of the fragments decreased by 60% (5 vs. 1.75) although survival and growth rate increased at first with 50% FC and 75% FC. Maximum sprouting and growth were found at 50% field capacity. Field capacity does affect the sprouting capacity of alligatorweed fragments but it has only a little influence on growth parameters. The results suggest that alligatorweed can sustain dry conditions to a great extent and also has the ability to sprout and grow in fully submerged soils.